1994
DOI: 10.1346/ccmn.1994.0420107
|View full text |Cite
|
Sign up to set email alerts
|

Acidified Oxalate and Dithionite Solubility and Color of Synthetic, Partially Oxidized Al-Magnetites and Their Thermal Oxidation Products

Abstract: Abstraet--Submicron-sized (~3-60 nm) powders of Al-substituted magnetite were synthesized in the laboratory by precipitation methods by mixing appropriate molar volumes FeCI2, FeC13 and A1CI3 solutions and precipitating with 20% NH4OH. Precipitates were dialyzed for 48 hr to remove excess salts and then freeze-dried. The nominal A1 mole fractions [AL = A1/(Al + Fe)] in the initial precipitate ranged from 0.001 to 0.42. Portions of the resulting powders were heated sequentially in air at 400* and 500"C. Powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Modifications or alternatives to the pyrophosphate and ammonium oxalate treatments have been proposed, , but have not been adopted widely. Recent refinements to the ammonium oxalate treatment have mainly involved the duration of the treatment or X-ray diffraction monitoring to determine coincident dissolution of the Fe oxides. ,, X-ray monitoring is particularly useful for soils that may contain magnetite, which also is soluble in oxalate. , The use of ammonium oxalate and EDTA, and the effects of adsorbed anions such as phosphate, were discussed by Borggaard; , the EDTA reagent, however, requires 3−7 months for extraction. For this reason, and because comparative tests on soils indicate that the amounts of Fe extractable by oxalate and by EDTA are similar (Figure ), EDTA seems not to be used extensively.…”
Section: Differential Dissolutionmentioning
confidence: 99%
“…Modifications or alternatives to the pyrophosphate and ammonium oxalate treatments have been proposed, , but have not been adopted widely. Recent refinements to the ammonium oxalate treatment have mainly involved the duration of the treatment or X-ray diffraction monitoring to determine coincident dissolution of the Fe oxides. ,, X-ray monitoring is particularly useful for soils that may contain magnetite, which also is soluble in oxalate. , The use of ammonium oxalate and EDTA, and the effects of adsorbed anions such as phosphate, were discussed by Borggaard; , the EDTA reagent, however, requires 3−7 months for extraction. For this reason, and because comparative tests on soils indicate that the amounts of Fe extractable by oxalate and by EDTA are similar (Figure ), EDTA seems not to be used extensively.…”
Section: Differential Dissolutionmentioning
confidence: 99%
“…1982, 1985; Phillips & Lovley 1987; Fine & Singer 1989; Borggaard 1990; Canfield et al . 1992; Golden et al . 1994; Pinheiro‐Dick & Schwertmann 1996; Rozan et al .…”
Section: Introductionmentioning
confidence: 99%
“…1971; Schwertmann 1973; Walker 1983; Borggaard 1988, 1990; Fine & Singer 1989). Others reported that the method can be applied to dissolve specific minerals, such as magnetite, and that differentiation on the basis of mineralogy would be possible with this method (Chao & Zhou 1983; Golden et al . 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The application of NIR has shown significant developments in geology (Golden et al 1 and Post et al 2 ) and in material science (Beck et al 3 ). The NIR analysis of soils and soil components began in early seventies.…”
Section: Introductionmentioning
confidence: 99%